2020
DOI: 10.3390/jcm9020279
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Ilizarov Bifocal, Acute Shortening and Relengthening with Bone Transport in the Treatment of Infected, Segmental Defects of the Tibia

Abstract: This prospective study compared bifocal acute shortening and relengthening (ASR) with bone transport (BT) in a consecutive series of complex tibial infected non-unions and osteomyelitis, for the reconstruction of segmental defects created at the surgical resection of the infection. Patients with an infected tibial segmental defect (>2 cm) were eligible for inclusion. Patients were allocated to ASR or BT, using a standardized protocol, depending on defect size, the condition of soft tissues and the state of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 33 publications
1
35
1
Order By: Relevance
“…This difference may be explained by the higher number of unplanned surgeries performed in the bone transport group to secure docking site union and remove the frame earlier (0.89 additional procedures per patient with bone transport, compared to 0.3 per patient with ASR). These results with bone union are similar to other series of Ilizarov method in infected tibial non-union with minimal use of flaps (Tetsworth et al, 2017;Eralp et al, 2016;Khan et al, 2015).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…This difference may be explained by the higher number of unplanned surgeries performed in the bone transport group to secure docking site union and remove the frame earlier (0.89 additional procedures per patient with bone transport, compared to 0.3 per patient with ASR). These results with bone union are similar to other series of Ilizarov method in infected tibial non-union with minimal use of flaps (Tetsworth et al, 2017;Eralp et al, 2016;Khan et al, 2015).…”
Section: Discussionsupporting
confidence: 87%
“…Cases were classified using the Cierny-Mader classification (Cierny et al, 2003) for osteomyelitis and Weber and Cech (1976) for infected non-unions. Ilizarov techniques were categorized on how the frame was used into: (1) protective, if used purely to protect the bone from fracture, or stabilize a simple fracture without major bone loss following debridement, (2) monofocal compression for mobile non-unions, (3) monofocal distraction for stiff non-unions, (4) bifocal acute shortening and relengthening (ASR) and (5) bone transport (McNally et al, 2017;Sigmund et al, 2020;Tetsworth et al, 2017;Ferreira et al, 2015).…”
Section: Data Collectionmentioning
confidence: 99%
“…As the first and basic stage of treatment process, infection elimination mainly includes segmental bone resection, extensive soft tissue debridement, and postoperative antibiotics application, aiming to remove infected focus radically and provide a satisfying environment for secondary reconstruction. Conventionally the second-stage reconstruction is carried out 6–8 weeks or months later, after the symptoms of infection have completely disappeared and the inflammatory markers have reduced to normal levels [ 6 ], by means of Masquelet technique [ 7 , 8 ], vascularized fibular grafts [ 9 ], cancellous bone grafting [ 10 ] or Ilizarov segmental bone transport [ [11] , [12] , [13] ]. In total, the entire hospital stay for post-traumatic osteomyelitis treatment usually takes several weeks or even months, during which patients have to endure two episodes of invasive operations, regardless of the failure of therapy and sharply increased financial costs.…”
Section: Introductionmentioning
confidence: 99%
“…At present, the Ilizarov bone transport technique seems to be a more convenient and effective method in the reconstruction of an infected defect, as it permits not only gradually restoring the integrity of lower extremity, but correcting the limb deformity, joint contractures and allowing early weight bearing [ 11 ]. Additionally, the distinction of Ilizarov bone transport technique from other reconstruction techniques is that its bone regeneration process occurs at the aseptic distraction zone outside the infection focus [ 11 ], thus avoiding direct interference from the infected area. Furthermore, today’s progress of debridement guidelines and the introduction of degradable local antibiotic carriers [ [14] , [15] , [16] ] also help remove infected tissues radically and eradicate the residual pathogens more efficiently.…”
Section: Introductionmentioning
confidence: 99%
“…However, research on the risk factors of recurrence of infection after surgery is rare. Studies have showed that the infection recurrence rate after treatment of posttraumatic tibial osteomyelitis with bone defect can reached to 10%-20% [16] . In this study, infection recurrence rate in the treatment of post-traumatic tibial osteomyelitis by using Ilizarov technique was 11.41%, which was consisted with previously reported study [17] , which also con rms that the Ilizarov technique is safe and effective treatment option in treatment of post-traumatic tibial osteomyelitis.…”
Section: Discussionmentioning
confidence: 99%